Cognitive-behavioral therapy for insomnia with objective short sleep duration phenotype: A systematic review with meta-analysis. (February 2023) - He, Dongmei; Guo, Zhiwei; Mcclure, Morgan A.; Mu, Qiwen; Jiang, Binghu
Abstract: Cognitive-behavioral therapy for insomnia (CBT-I) has been recommended as the first-line therapy for this condition. However, insomnia disorder with objective short sleep duration (ISS) phenotype is a distinct subtype from insomnia with normal sleep duration (INS) phenotype, and it may have a differential therapeutic response. We searched PubMed, EMBASE, Cochrane Library, and ClinicalTrials.gov using the PICOS principle for studies that examined the efficacy of cognitive-behavioral therapy for those with the ISS phenotype versus the INS phenotype, and identified nine studies with 612 patients with insomnia disorder. This included 270 patients with the ISS phenotype and 342 patients with the INS phenotype. The main outcome was that CBT-I had a better efficacy for the INS phenotype compared with the ISS phenotype, with about 30% higher response and about 20% higher remission. Similar results were indicated in the secondary outcomes. The therapeutic response of the ISS phenotype was significantly different from that of the INS phenotype. In the future, research is needed to clarify how to optimally treat insomnia disorder with the ISS phenotype in prospective randomized clinical trials, and to understand whether decreasing physiologic arousal will be necessary to improve results.